Electrically tunable microwave properties in NiFeTa/[Pb(Mg1/3Nb2/3)O3]0.68-[PbTiO3]0.32(011) magnetoelectric heterostructures - Phuoc, N.N. (American Institute of Physics Inc., 2016)
10.1063/1.4908548